Efektivitas Penilaian Pembelajaran Menggunakan Google Form pada Pembelajaran Daring - Munawaroh, Rahmah Zaqiyatul; Prastowo, Andi; Nurjanah, Maya (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Learning in the network implemented in pandemic covid-19 is a new challenge for the Indonesian learning system. The demands of more creativity are left to the educators for effective learning. So, too, with new options/ideas associated with the learning system, especially with the student learning assessment system. The feature of the Google form on the Google application becomes one of the options that can be used to facilitate the student learning assessment process. The study is conducted to learn the effectiveness of learning assessments using Google form on students, the strengths and deficiencies of Google form, and the knowledge of barriers students experience when using Google form. Research is conducted with a descriptive qualitative method with the data-collection of interviews and questionnaires. The results of the study say that the use of the learning assessment using Google form is considered to be effective because it makes it easier for teachers and students, both in filling out problems and process processes by teachers. Google form has an advantage such as providing an automated data-processing system, so teachers don't have to manually calculate. The barriers are affected by network activity, and the lack of understanding of students or guardians of technology.